Haemolytic and phospholipase C (PLC) activities of Rhodococcus equi - Smola, J; Katerov, V; Schalén, C (The Journal of applied bacteriology, 1994)
Rhodococcus equi, an intracellular organism causing pneumonia and lung abscesses in foals, is generally thought to be non-haemolytic. In the present study, however, 13 of 14 representative isolates were found to be haemolytic when tested on agar media containing washed red blood cells rather than whole blood. Red cells of rabbits, dogs, horses and man were more sensitive to lysis than were those of ruminants. Two new enzymatic activities of the species were defined: a lecithinase and a phosphatidylinositol-specific phospholipase C (PI-PLC). As judged from tests for trypsin, temperature and ethanol sensitivity, the haemolytic activity was primarily dependent on PI-PLC though the participation of lecithinase seemed probable. The haemolytic activity of growing strains, but not of cell-free preparations, was partially inhibited by lecithin but enhanced by cholesterol; however, cholesterol oxidase (CO) activity, known to mediate cooperative lysis of RBC sensitized with sphingomyelin-specific phospholipases C or D of some other species, did not contribute to the direct haemolysis caused by R. equi as demonstrated here.
Keywords: Actinomycetales Infections; psi; Sensitivity and Specificity; senzitivita a specificita; Humans; nemoci koní; druhová specificita; Dogs; Erythrocytes; Hemolysis; Rhodococcus equi; Horses; Type C Phospholipases; lidé; fosfolipasy typu C; koně; zvířata; infekce bakteriemi řádu Actinomycetales; erytrocyty; Species Specificity; králíci; Horse Diseases; Animals; hemolýza; Rabbits